Efektivitas Implementasi Standar Isi dalam Pembelajaran Pendidikan Agama Islam: Studi Kualitatif Di Madrasah Tsanawiyah - Zia Achmalia Adela; Ananda Siti Nurpadilah; Siti Khoerunnisa; Saskia Nur Sya'bani; Hinggil Permana (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Raising the standard of education is fundamental in building character and competencies of individuals as part of human resource development. Learning through Islamic Religious Education (PAI) becomes a foundation for cultivating students’ ability to regulate themselves and religious character. Content Standards, as part of the National Education Standards (SNP), serve as the main reference in the curriculum and learning in madrasas, including MTs Al-Fathimiyyah, which integrates the official curriculum with pesantren-based enrichment. The study is intended to present an overview of the practice of Content Standards in Islamic Religious Education learning at MTs Al-Fathimiyyah, identify the challenges faced, and evaluate the effectiveness of competency achievement in accordance with national standards. The research is intended to examine the practice of applying Content Standards within the Islamic Religious Education subject at MTs Al-Fathimiyyah, identify challenges faced, and evaluate the effectiveness of competency achievement in accordance with national standards. The implementation of Content Standards at MTs Al-Fathimiyyah has shown positive developments in Islamic Religious Education learning, but further enhancement is necessary with respect to teacher understanding, communication with parents, and learning evaluation. Recommendations include ongoing training for teachers, increased dialogue with parents, and the development of a comprehensive evaluation system so that the quality of learning and student competency achievement can be optimized.